Anti-Galectin-2 Antibody Treatment Reduces Atherosclerotic Plaque Size and Alters Macrophage Polarity - Kane, Jamie; Jansen, Matthijs; Hendrix, Sebastian; Bosmans, Laura A.; Beckers, Linda; Tiel, Claudia van; Gijbels, Marion; Zelcer, Noam; Vries, Carlie J. de; von Hundelshausen, Philipp; Vervloet, Marc; Eringa, Ed; et al. (Thrombosis and haemostasis, 2022)
Abstract Background Galectins have numerous cellular functions in immunity and inflammation. Short-term galectin-2 (Gal-2) blockade in ischemia-induced arteriogenesis shifts macrophages to an anti-inflammatory phenotype and improves perfusion. Gal-2 may also affect other macrophage-related cardiovascular diseases. Objectives This study aims to elucidate the effects of Gal-2 inhibition in atherosclerosis. Methods